2015
DOI: 10.4103/2249-4863.161349
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about diabetes and relationship between compliance to the management among the diabetic patients from Rural Area of Sangli District, Maharashtra, India

Abstract: Introduction:Diabetes is an important public health problem of India. Studies have shown that increase in patients’ knowledge regarding the disease results in better compliance to treatment and decrease in complications. This study was planned to assess the knowledge about diabetes and its correlation with pharmacological and non-pharmacological compliance, among the diabetic patients attending rural health center from Sangli District, Maharashtra (India).Materials and Methods:The study was conducted during Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Studies done in southern Karnataka and rural Maharashtra, which employed self-reported compliance by patients, reported a compliance of 83.6% and 76.2%, respectively, among diabetics. [1314] Further studies by Bansal et al . in rural Ludhiana and Santhanakrishnan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in southern Karnataka and rural Maharashtra, which employed self-reported compliance by patients, reported a compliance of 83.6% and 76.2%, respectively, among diabetics. [1314] Further studies by Bansal et al . in rural Ludhiana and Santhanakrishnan et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, self-reported compliance was used in studies done in coastal south India and rural Maharashtra where compliance was found to be 83.9% and 76.2%, respectively. [ 10 19 ] Compliance, as elicited by the Morisky Medication Adherence Scale, was used in a Tertiary Care Centre in Kerala where the compliance was found to be 64.8%. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 ] The compliance rates to oral hypoglycemic agents (OHAs) have been found to range from 60% to 75% among patients attending various tertiary care centers from different regions of the India[ 7 8 9 ] and compliance has been found to be affected by knowledge and educational status of the patients. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…The findings point to a major deficiency in these patients' health care practices that need to be addressed by their providers. In congruence with this, a study in India revealed low adherence to diabetes management among type-2 DM patients, and this was attributed to their lack of related knowledge (Chavan et al, 2015). On the same line, a study in Italy showed that only approximately 40% of the patients were adherent to their medications (Napolitano et al, 2015).…”
Section: Discussionmentioning
confidence: 53%